Management of Collaborative Academic Supervision Training for School Supervisory Teams in Papua - Reinhard Leonardo Paais; Yari Dwikurnaningsih; Marinu Waruwu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study aims to describe the management of collaborative academic supervision training for school supervisory teams in Papua, focusing on the stages of planning, organizing, implementation, and evaluation. The study employed a mixed-method approach using an exploratory sequential design, involving 12 members of school supervisory teams from four schools in Sorong Regency, Southwest Papua Province, selected through purposive sampling. Data were collected through interviews, observations, tests, and questionnaires. All instruments were validated by experts and pilot-tested in the field to ensure their validity and reliability. The results indicate that the training was implemented systematically, smoothly, and through online sessions via Zoom, resulting in a significant improvement in participants’ understanding, with mean scores increasing from 48.75 to 77.92 (p = 0.000), and 83% of participants achieving the success criteria, while the training process evaluation was categorized as very good with an average score of 86.30%. These findings confirm that structured collaborative supervision training supported by digital platforms can effectively enhance supervisory competence and contribute to the improvement of instructional leadership in schools, including in remote areas.